2010
DOI: 10.1002/mar.20341
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of manipulative intent and cognitive resources on the evaluation of narrative ads

Abstract: This research examines how salience of manipulative intent affects the evaluation of ads that are presented in a narrative or expository format. Study 1 shows that when manipulative intent is not salient, narrative ads are evaluated more positively than expository ads because they trigger a narrative processing style. When manipulative intent is salient, however, consumers regard the advertiser's tactics more suspiciously and adopt an analytical processing style to evaluate both narrative and expository ads. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 42 publications
2
69
0
Order By: Relevance
“…Cognitive deliberation on injunctive norms may increase these effects, whereas cognitive load decreases them. After all, when consumers are under cognitive load, they are less likely to perceive a persuasive message as manipulative (Wentzel, Tomczak, & Herrmann, 2010) and therefore are less likely to resist it.…”
Section: Cognitive Deliberation and Norm Formulationmentioning
confidence: 96%
“…Cognitive deliberation on injunctive norms may increase these effects, whereas cognitive load decreases them. After all, when consumers are under cognitive load, they are less likely to perceive a persuasive message as manipulative (Wentzel, Tomczak, & Herrmann, 2010) and therefore are less likely to resist it.…”
Section: Cognitive Deliberation and Norm Formulationmentioning
confidence: 96%
“…When the manipulative intent of a message is inferred a change of meaning can occur, and the viewer may adapt a more critical processing style, which may influence the evaluation of the sender (Campbell 1995;Campbell and Kirmani 2000;Wentzel, Tomczak, and Herrmann 2010), which is the brand in this case. Prior studies have indeed demonstrated that brand placement disclosures affect brand responses, such as brand memory and brand attitudes (e.g., Boerman, Van Reijmersdal, and Neijens 2012a;Campbell, Mohr, and Verlegh 2013;Van Reijmersdal, Tutaj, and Boerman 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 97%
“…When persuasion knowledge is activated, people may adopt a more critical processing style and evaluate the persuasive message suspiciously (Campbell 1995;Campbell and Kirmani 2000;Wentzel, Tomczak, and Herrmann 2010). As a result, the activation of persuasion knowledge can lead to diminished persuasion (Buijzen, Van Reijmersdal, and Owen 2010).…”
Section: Brand Attitudementioning
confidence: 97%
“…These studies show that consumers negatively respond to religious advertising (McDaniel, ) and pharmaceutical marketing (McGraw et al., ). When an advertisement exhibits a salient manipulative intent through the employment of biased endorsers (Kirmani & Zhu, ), excessive use of rhetorical questions (Ahluwalia & Burnkrant, ) or borrowed interest appeals (Campbell, ), consumers evaluate the ads negatively, even if the ads are narrative in nature (Wentzel et al., ). Prominent product placement also results in negative brand attitude.…”
Section: Introductionmentioning
confidence: 99%